An SCA ASIC-based multi-channel readout system for a prototype multi-purpose TPC at CSNS Back-n white neutron source. Issue 1 (1st November 2022) - Chen, Zhen; Feng, Changqing; Chen, Haolei; Fan, Ruirui; Yi, Han; Wang, Jiaqi; Liu, Shubin
Abstract : The back-streaming white neutron source (Back-n) at China Spallation Neutron Source (CSNS), which has excellent energy spectrum and good time resolution, provides superior conditions for neutron induced light charged particle tracking experiment. To track light charged particles, CSNS has proposed a project named Multi-purpose Time Projection Chambers (MTPC) and completed a 1519-channel prototype. A multi-channel readout system based on Switched Capacitor Arrays (SCA) waveform sampling ASIC was designed to meet the requirements of the prototype MTPC. This paper presents the structure of this readout system and the results of the beam test with MTPC at CSNS. Time of Flight spectrum of neutron beam and 3D-track of neutron induced light charged particles were successfully reconstructed. These test results prove the feasibility of large-scale MTPC.